Evaluasi Model Kirkpatrick terhadap Kegiatan Desain Camp #1: Bamboo for Creative Millennials - Kristian Oentoro (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2020)
Design Camp #1 is the national workshop for product design students which involve 28 stu participants from 14 public/private colleges in Indonesia. The theme of Bamboo for Creative Millennials was raised to encouraged the participants to work together with bamboo craftsmen at Sendari Bamboo Crafts Center, Sleman, D.I. Yogyakarta. As the first program carried out, Design Camp # 1 requires evaluative research so that the process of implementing the next activity can continue to be developed. The Kirkpatrick model is applied to find out four levels of evaluation, including reactions, learning, behavior, and results. The research method used is quantitative descriptive, while the data collection uses interview techniques and online surveys. The results of the reaction evaluation showed that 52.5% of participants were very satisfied with aspects of the implementation (design materials, craft mentors, organizers, and support of each college). Learning evaluation shows that participants can learn bamboo processing skills (75%) and knowledge of bamboo design (67.8%). Participants also showed good collaboration in the work process, even in the evaluation of behavior 38% of aspects of success were determined by a group of friends. Design Camp # 1 activity produced 10 prototypes and 67.8% of participants were interested in developing their design ideas. The evaluation results also showed that 60.7% of participants strongly agreed that this activity could support a career as a product designer.Key words: design, evaluation, Kirkpatrick, bamboo